Comparative palatability of orally disintegrating tablets (ODTs) of Praziquantel (L-PZQ and Rac-PZQ) versus current PZQ tablet in African children: A randomized, single-blind, crossover study. - Muhidin K Mahende; Eric Huber; Elly Kourany-Lefoll; Ali Ali; Brooke Hayward; Deon Bezuidenhout; Wilhelmina Bagchus; Abdunoor M Kabanywanyi (Public Library of Science (PLoS), 2021)
Background Praziquantel (PZQ) is currently the only recommended drug for infection and disease caused by the schistosome species that infects humans; however, the current tablet formulation is not suitable for pre-school age children mainly due to its bitterness and the large tablet size. We assessed the palatability of two new orally disintegrating tablet (ODT) formulations of PZQ. Methodology This randomized, single-blind, crossover, swill-and-spit palatability study (NCT02315352) was carried out at a single school in Tanzania in children aged 6-11 years old, with or without schistosomiasis infection as this was not part of the assessment. Children were stratified according to age group (6-8 years or 9-11 years) and gender, then randomized to receive each formulation in a pre-specified sequence. Over 2 days, the children assessed the palatability of Levo-Praziquantel (L-PZQ) ODT 150 mg and Racemate Praziquantel (Rac-PZQ) ODT 150 mg disintegrated in the mouth without water on the first day, and L-PZQ and Rac-PZQ dispersed in water and the currently available PZQ 600 mg formulation (PZQ-Cesol) crushed and dispersed in water on the second day. The palatability of each formulation was rated using a 100 mm visual analogue scale (VAS) incorporating a 5-point hedonic scale, immediately after spitting out the test product (VASt = 0 primary outcome) and after 2-5 minutes (VASt = 2-5). Principal findings In total, 48 children took part in the assessment. Overall, there was no reported difference in the VASt = 0 between the two ODT formulations (p = 0.106) without water. Higher VASt = 0 and VASt = 2-5 scores were reported for L-PZQ ODT compared with Rac-PZQ ODT in older children (p = 0.046 and p = 0.026, respectively). The VASt = 0 and VASt = 2-5 were higher for both ODT formulations compared with the standard formulation (p<0.001 for both time points). No serious adverse events were reported. Conclusions/significance The new paediatric-friendly formulations dispersed in water were both found to be more palatable than the existing standard formulation of PZQ. There may be gender and age effects on the assessment of palatability. Further research is needed for assessing efficacy and tolerability of the newly ODTs Praziquantel drug in younger children. Trial registration The trial was registered on ClinicalTrials.gov (NCT02315352) and in the Pan African Clinical Trials Registry (PACTR201412000959159).